Features of the manifestation and course of Crohn’s disease in three brothers - A. V. Morkovina; E. Yu. Yuryeva; T. L. Lapina; P. V. Pavlov; A. S. Tertychnyy; A. A. Sheptulin (Сеченовский вестник, 2020)
Hereditary predisposition is the most significant risk factor for Crohn’s disease (CD) in siblings. Case reports. CD was diagnosed in 3 brothers in a family with 6 children of the same generation: the disease manifested itself in one — at the age of 15 years and in two brothers — at the age of 17 years. In the older brother, CD manifested with acute intestinal obstruction, ileum perforation, diffuse peritonitis; in the middle — with symptoms similar to appendicular infiltrate. Both brothers underwent resection of the terminal ileum, cecum, and part of the ascending colon with the imposition of ileoascendoanastomosis. The younger brother was diagnosed with a non-stricturing, non-penetrating form of CD with a gradual onset and no complications. Among the siblings without CD, two have rheumatoid arthritis and vitiligo. Discussion. Similar signs of the familial form of CD were young age of manifestation and ileocolonic disease location; distinctive signs — the presence of complications and surgical interventions in only two brothers. A special feature of the case reports is the CD development only in boys and the combination of three different autoimmune diseases in one generation of the family.